The role of community resources for sustainable tourism practice of Mah Meri indigenous community of Malaysia - Kunasekaran, Puvaneswaran; Gill, Sarjit S.; Ramachandran, Sridar (2016)
This paper presents the significant role of resources which is utilized by the Mah Meri community in Pulau Carey, Malaysia to practice sustainable tourism. Preliminary study was conducted at Kampung Sungai Bumbon which is a well established indigenous tourism destination in Malaysia. In-depth interview which was used as the qualitative data collection method helped the researchers to holistically understand the community resources which can encourage sustainable tourism practice. Natural tourism products like wood carvings and weavings are the main attributes which contribute to tourism development. This study reveals that the community is proud of its diversified environment .However, the community feels that their culture and tourism gradually facing great threat because of the scarcity of natural resources. It is hoped that the findings of this study will contribute to existing literature in the indigenous tourism and community resources ground.